Combate à corrupção e integridade pública: estudo das IFES de Minas Gerais - Oliveira, Jamile Camargos de (2020)
Corruption in Public Administration has been highlighted in recent years in Brazil, acquiring greater centrality due to the successive scandals unveiled in the country. The Federal Public Institutions of Higher Education (IFES) did not pass unscathed in this context, calling special attention to the fact that they are organizations aimed at promoting intellectual and citizen education. This dissertation analyzed how the organizational environment is configured to fight corruption in IFES. Qualitative, descriptive and explanatory research was carried out through a case study in all 17 IFES in Minas Gerais. For that, the characteristics related to corruption were verified in 49 Administrative Disciplinary Processes (PADs) initiated between 2015 and 2019 and 11 civil servants who participated in the establishment and / or conduction of these processes were interviewed, to investigate the dynamics of control corruption in those IFES in the light of public integrity. The research findings indicated that the main factors of the organizational environment related to public integrity that contribute to the fight against corruption in the IFES correspond to the channels for expressing complaints, the external control mechanisms and internal control, the instruments for promoting ethics and rules conduct, expansion of transparency and access to information. It was found that the IFES corporatism and structural bottlenecks correspond to the main obstacles of the organizational environment in the fight against corruption. From a theoretical point of view, the study contributed to the discussion of a topic that has been little investigated in the context of the IFES. From a practical point of view, it demonstrated the difficulties encountered by IFES in facing corruption due to structural deficiencies and notably lack of servers, as well as a correction unit. In social terms, it contributed to the identification of mechanisms that can be used to curb and prevent a phenomenon that causes serious damage to education. We suggest the development of future research aimed at verifying the institutionalization of public integrity measures in the IFES as a strategy to combat corruption.